Are Hemodynamics Surrogate End Points in Pulmonary Arterial Hypertension? - Ventetuolo, Corey E.; Gabler, Nicole B.; Fritz, Jason S.; Smith, K. Akaya; Palevsky, Harold I.; Klinger, James R.; Halpern, Scott D.; Kawut, Steven M. (Circulation (New York, N.Y.), 2014)
BACKGROUND—Although frequently assessed in trials and clinical practice, hemodynamic response to therapy has never been validated as a surrogate end point for clinical events in pulmonary arterial hypertension (PAH). METHODS AND RESULTS—We performed a patient-level pooled analysis of 4 randomized, placebo-controlled trials to determine whether treatment-induced changes in hemodynamic values at 12 weeks accounted for the relationship between treatment assignment and the probability of early clinical events (death, lung transplantation, atrial septostomy, PAH hospitalization, withdrawal for clinical worsening, or escalation in PAH therapy). We included 1119 subjects with PAH. The median (interquartile range) age was 48 years (37–59 years), and 23% were men. A total of 656 patients (59%) received active therapy (101 [15%] iloprost, 118 [18%] sitaxsentan, 204 [31%] sildenafil, and 233 [36%] subcutaneous treprostinil). Active treatment significantly lowered right atrial pressure, mean pulmonary artery pressure, and pulmonary vascular resistance and increased cardiac output and index (P<0.01 for all). Changes in hemodynamic values (except for right atrial pressure and mean pulmonary artery pressure) were significantly associated with the risk of a clinical event (P<0.02 for all). Although active treatment approximately halved the odds of a clinical event compared with placebo (P<0.001), changes in hemodynamics accounted for only 1.2% to 13.9% of the overall treatment effect. CONCLUSIONS—Treatment-induced changes in hemodynamics at 12 weeks only partially explain the impact of therapy on the probability of early clinical events in PAH. These findings suggest that resting hemodynamics are not valid surrogate end points for short-term events in PAH clinical trials.